ANIMOSITY’S EFFECTS ON CONSUMER BEHAVIOR: A STUDY OF FINNISH CONSUMER ANIMOSITY TOWARDS RUSSIA - Horstia, Matti (My University, 2017)
The goals of this thesis for the literature review’s part are to 1) Explain what consumer animosity is 2) Study the most common sources of consumer animosity 3) Clarify how consumer animosity functions under different circumstances 4) Examine consumer animosity’s effects on consumer behavior 5) Offer practical implications in managing consumer animosity from managerial and governmental standpoints. The empirical study was conducted as an online survey, to which 149 Finnish consumers participated. The empirical goals of the this thesis are to 1) Find out to what degree Finnish consumers feel animosity towards Russia 2) Study how animosity towards Russia in Finnish consumers affects their consumer behavior towards Russian goods, and tourism to Russia 3) Examine sources behind the Finnish consumer animosity towards Russia 4) Research whether demographic factors have an impact on Finnish consumers’ animosity towards Russia. The results support previous consumer animosity literature in consumer animosity lowering willingness to buy from the animosity country. The results also show that consumer animosity, and people animosity in particular, decreases willingness to visit the animosity country as a tourist. The findings also give strong support for consumer animosity decreasing product quality judgments concerning products originating from the animosity country. It was found out that age is significantly and positively correlated with Finnish consumers’ animosity towards Russia. Also consumers living in the capital expressed more animosity than those living outside the capital. Gender had no effect on the level of consumer animosity towards Russia in Finnish consumers. The most commonly expressed reasons for consumer animosity towards Russia were war related, and politics related. Lastly, it was found out that despite previous war history between Finland and Russia, Finnish consumers see Russia’s more recent actions as harder to forgive. Also managerial implications based on the results are presented.
Keywords: consumer animosity; country of origin; fi=Markkinointi|en=Marketing|; fi=Master's Degree Programme in International Business|